The Influence of Self-Efficacy, Teaching Skills, and School Field Introduction (PLP) on UNNES Students' Interest in - Rahman, Elvian Ibnu; Arif Wahyu Wirawan (Journal of Practice Learning and Educational Development, 2025)
This study examines the influence of self-efficacy, teaching skills, and the School Field Introduction Program (PLP) on the interest in becoming a teacher among students of the Office Administration Education program at Universitas Negeri Semarang. Using a quantitative associative-causal approach, data were collected through closed questionnaires from 139 students in the 2021 batch. Multiple regression analysis revealed that self-efficacy, teaching skills, and PLP collectively had a significant positive effect (F = 77.009, p < 0.05), explaining 63.1% of the variance in teaching interest. However, partial analysis showed that only self-efficacy had a significant individual impact (t = 7.048, p < 0.05, contribution = 26.93%), while teaching skills (t = 0.818, p > 0.05) and PLP (t = 0.627, p > 0.05) did not. The findings suggest that while all three factors contribute to teaching interest, self-efficacy is the most critical determinant. This implies that strengthening self-confidence is essential for fostering teaching aspirations, whereas teaching skills and field experience alone may not suffice. The study highlights the need for holistic teacher preparation programs that emphasize psychological and motivational aspects alongside technical competencies.